Social cognition in schizophrenia: Factor structure of emotion processing and theory of mind. (30th August 2016) - Browne, Julia; Penn, David L.; Raykov, Tenko; Pinkham, Amy E.; Kelsven, Skylar; Buck, Benjamin; Harvey, Philip D.
Abstract: Factor analytic studies examining social cognition in schizophrenia have yielded inconsistent results most likely due to the varying number and quality of measures. With the recent conclusion of Phase 3 of the Social Cognition Psychometric Evaluation (SCOPE) Study, the most psychometrically sound measures of social cognition have been identified. Therefore, the aims of the present study were to: 1) examine the factor structure of social cognition in schizophrenia through the utilization of psychometrically sound measures, 2) examine the stability of the factor structure across two study visits, 3) compare the factor structure of social cognition in schizophrenia to that in healthy controls, and 4) examine the relationship between the factors and relevant outcome measures including social functioning and symptoms. Results supported a one-factor model for the patient and healthy control samples at both visits. This single factor was significantly associated with negative symptoms in the schizophrenia sample and with social functioning in both groups at both study visits. Highlights: Utilized only the most psychometrically sound measures of social cognition. Results supported a one-factor model of social cognition in schizophrenia. Single factor was associated with negative symptoms and social functioning. Results supported similar factor structure and correlations in healthy controls. Factor structure of social cognition was stable over time in both groups.